The curricular plan and the professional profile of the withdrawn of the faculty of infirmary of national university Hermilio Valdizán of Huánuco 2007 - Veramendi Villavicencio, Nancy (2009)
To determine the relation between the Curricular Plan and the professional profile of the withdrawn one of infirmary in study. A corelational study with 21 withdrawn was designed and 25 educational ones of the Faculty of Infirmary of National University Hermilio Valdizán of Huánuco, during the period of 2007. The data obtained from a questionnaire and test of performance evaluation. An analysis bivaried by means of the coefficient of PEARSON correlation was made. 71,4% of the withdrawn ones reached a superior performance, 28,6% of average and from no withdrawn it arrived at the level from inferior. In the valuation of the curricular situation 52,4% of the withdrawn ones indicate that it does not have with gravity, whereas the educational ones in 52, 0% assure a problem moderately burdens. As far as the correlation between the curricular plan and the professional profile the coefficient was of 0.685 which was significant (P = 0.001). And in the dimensions of curricular programming and conduction and evaluation of subjets with the profile of the withdrawn one they were with statistically significant quantitative relations (P< 0, 05). The present situation of the curricular Plan and the profile of the withdrawn one in infirmary demonstrate significant relations, in where the situation of the curricular Plan also advances makes the performance of the withdrawn one.